Liraglutide Alleviates Hepatic Steatosis and Liver Injury in T2MD Rats via a GLP-1R Dependent AMPK Pathway - Zhou, Rui; Lin, Chuman; Cheng, Yanzhen; Zhuo, Xiaoyun; Li, Qinghua; Xu, Wen; Zhao, Liang; Yang, Li (Frontiers in Pharmacology, 2021)
Nonalcoholic fatty liver diseases (NAFLD) ranging from non-alcoholic fatty liver to non-alcoholic steatohepatitis have a high preference in Type 2 diabetes mellitus (T2DM) patients. However, no anti-diabetic drug is approved for the treatment of NAFLD in T2DM patients. Although multiple daily injection of basal-bolus insulin is the final therapeutic process for T2DM, we found that insulin treatment aggravated hepatic steatosis and oxidative stress in ZDF rats. Here, besides glycemic control, we demonstrated a stimulatory role of liraglutide in relieving hepatic steatosis and liver injury in ZDF rats. Interestingly, liraglutide could also alleviate the insulin aggravated hepatic fatty accumulation. GLP-1 agonist (liraglutide and Ex-4) activated the expression of peroxisome proliferator-activated receptor α (PPARα) via a GLP-1R dependent AMPK pathway. As a nuclear transcription factor, PPARα could mediate the effect of GLP-1 in alleviating hepatic steatosis through differentially regulating the expression of its targeting genes including acetyl CoA carboxylase (ACC) and carnitine palmitoyl transferase la (CPT1a) both in vitro and in vivo. Moreover, our results indicated that GLP-1 could relieve liver injury through decreasing the oxidative stress that stimulated by hepatic steatosis. Insulin might aggravate hepatic steatosis and liver injury through inhibiting the expression of GLP-1R. In this research, we investigated the feasibility of liraglutide treatment combined with basal insulin in attenuating hepatic steatosis and liver injury in ZDF rats，as well as the mechanism behind, which will provide a theoretical basis for the combination treatment recommended by the latest clinical practice guidelines for T2DM.